2010
DOI: 10.1021/ac100812c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle Enhanced Surface Plasmon Resonance Sensing and Its Application for the Ultrasensitive Detection of Magnetic Nanoparticle-Enriched Small Molecules

Abstract: Magnetic nanoparticles (MNPs) have been frequently used in bioseparation, but their applicability in bioassays is limited due to their extremely small size so that sensitive detection is difficult to achieve using a general technique. Here, we present an amplification technique using MNPs for an enhanced surface plasmon resonance (SPR) bioassay. The amplification effect of carboxyl group modified Fe(3)O(4) MNPs of two sizes on SPR spectroscopy is first demonstrated by assembling MNPs on amino group modified SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(80 citation statements)
references
References 46 publications
1
79
0
Order By: Relevance
“…S6 exhibits a typical Fe-O-Fe absorption bands of HOOC-MNP at 548 cm À 1 , and the C ¼O and O-H stretches of the COOH at $1710 cm À 1 and $ 3500 cm À 1 (Wang et al, 2010), which indicates the Carboxylic acid group was chemical bound on the surface of the Fe 3 O 4 MNP. Comparing with the FT-IR spectra of carboxyl-Fe 3 O 4 MNP, the characteristic peaks of N-H of the CONH at 3100-3600 cm À 1 were observed in the FT-IR spectrum of MNPAb.…”
Section: Characterization Of Covalently Immobilized Antibodies On Thementioning
confidence: 99%
“…S6 exhibits a typical Fe-O-Fe absorption bands of HOOC-MNP at 548 cm À 1 , and the C ¼O and O-H stretches of the COOH at $1710 cm À 1 and $ 3500 cm À 1 (Wang et al, 2010), which indicates the Carboxylic acid group was chemical bound on the surface of the Fe 3 O 4 MNP. Comparing with the FT-IR spectra of carboxyl-Fe 3 O 4 MNP, the characteristic peaks of N-H of the CONH at 3100-3600 cm À 1 were observed in the FT-IR spectrum of MNPAb.…”
Section: Characterization Of Covalently Immobilized Antibodies On Thementioning
confidence: 99%
“…Wang et al [117] developed a novel SPR sensor based on an indirect competitive inhibition assay (ICIA) for the detection of adenosine by employing Fe 3 O 4 MNPs-anti adenosine aptamer conjugates as the amplification reagent. Their results demonstrated that Fe 3 O 4 MNPs can be utilized as a powerful amplification agent to provide a sensitive way of detecting adenosine via SPR within the range of 10-10000 nmol/L, which is much lower than the detection results of a general SPR sensor.…”
Section: Signal Enhancer For Sprmentioning
confidence: 99%
“…MNP-based detection of biomolecules has been applied to both surface-based (Bruls et al 2009;Mani et al 2009;Nash et al 2012;Tekin et al 2013;Wang et al 2010;Wang and Gan 2009) and volume-based assays (Aurich et al 2006;Bamrungsap et al 2011;Chun et al 2011;Göransson et al 2010;Josephson et al 2001;Liang et al 2011;Liong et al 2013;Ranzoni et al 2012;Sun et al 2006;Zhang et al 2013a). The latter typically employs sandwich binding-induced clustering where a molecule of interest is bound to multiple receptors tethered onto MNP surfaces, resulting in the agglutination of MNPs.…”
Section: Introductionmentioning
confidence: 99%